2004
DOI: 10.1158/0008-5472.can-2902-2
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Regulation of Proliferation in Multicellular Spheroids Is Mediated through Differential Expression of Cyclin-Dependent Kinase Inhibitors

Abstract: Multicellular spheroids composed of transformed cells are known to mimic the growth characteristics of tumors and to develop gradients in proliferation with increasing size. This progressive accumulation of quiescent cells is presumably an active process that occurs in response to the microenvironmental stresses that develop within the three-dimensional structure, and, yet, little is known regarding either the signals that induce the cell cycle arrest or the molecular basis for the halt in proliferation. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 73 publications
(71 reference statements)
10
75
0
2
Order By: Relevance
“…It is supposed that p27 in nucleus binds to cyclin E-CDK2 complex and inactivates the complex in G0/G1 phase, but once p27 is transported to cytosol and degraded, the complex is activated and it triggers the transition from G1 to S phase. Our data were consistent with this kinetics of p27, so it was suggested that intranuclear p27 plays a central role for cellcycle quiescence in sphere forming cells (20)(21)(22).…”
Section: Discussionsupporting
confidence: 89%
“…It is supposed that p27 in nucleus binds to cyclin E-CDK2 complex and inactivates the complex in G0/G1 phase, but once p27 is transported to cytosol and degraded, the complex is activated and it triggers the transition from G1 to S phase. Our data were consistent with this kinetics of p27, so it was suggested that intranuclear p27 plays a central role for cellcycle quiescence in sphere forming cells (20)(21)(22).…”
Section: Discussionsupporting
confidence: 89%
“…MTS were dissociated into subpopulations of cells from different locations in the spheroid as described previously (31). The spheroids were placed in a cylindrical chamber with a 75-m nylon mesh.…”
Section: Hoechst 33258 and Propidium Iodide (Ho/pi) Double Stainingmentioning
confidence: 99%
“…In normal cells, the function of p21 is to ensure appropriate CDK inhibition during cell cycle progression. However, recent studies have demonstrated that p21 may also have an anti-apoptotic function, which enables the cells to proliferate under conditions that otherwise lead to apoptosis or arrest [8,38]. There has been no report of the relationship between p21 and lung cancer patients with cigarette-smoking history.…”
Section: Ho-1 In Lung Carcinogenesismentioning
confidence: 99%